Numerical analysis of selectively coated MMI structures for the application in optical sensor technology - Szewczuk, Artur; Błahut, Marek (Photonics Letters of Poland, 2015)
In this work the numerical analysis of an optical sensor based on multimode interference structures with the sensing layer which cover selectively multimode waveguide are presented. The analyzed gradient index optical waveguides are fabricated in sodium-potassium ion exchange process. The effects of the different shape of the sensing layer and excitation conditions are demonstrated. Full Text: PDF References K.R. Kribich et al., "Novel chemical sensor/biosensor platform based on optical multimode interference (MMI) couplers", Sens. Actuat. B-Chem 107, 188 (2005). CrossRef T. Mazingue et al., "Simulations of refractive index variation in a multimode interference coupler: Application to gas sensing", Opt. Comm., 278(2), 312 (2007). CrossRef A. Szewczuk, M. Blahut, "Polarization effects in K+?Na+ ion exchanged MMI structures with absorption cover", Optica Applicata, 43, 441 (2013). CrossRef A. Szewczuk, M. Blahut, "MMI Structures Covered by Bromocresol Purple for Ammonia Detection", Acta. Phys. Pol. A 124, 570 (2013). CrossRef A. Szewczuk, M. Blahut, "Impact of high index buffer layer on the improvement of the MMI sensor sensitivity", Photonics Lett. Poland 6(4), 127 (2014). CrossRef